By the Numbers: Focus on the Facts - University of Wisconsin-La Crosse (University of Wisconsin-La Crosse, 2006)
Selectivity & Yield: Measuring How Difficult It Is to Get In (December 2006) Editor's Note: Recent decisions by some of the nations more prestigious colleges and universities to eliminate early acceptance practices because they may provide undue advantage to students from higher income levels have spawned a furor of discussion about just how difficult it is to gain admittance to colleges and universities. Fanned further by controversies over affirmative action and the practice of considering student race and ethnicity in admissions, universities re under increasing scrutiny about who and how they admit to their hallowed halls.
Keywords: University of Wisconsin-La Crosse -- Statistics